2011
DOI: 10.1103/physrevlett.106.216401
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Carrier Concentration-Dependent Electronic Behavior in Layered Cobaltates

Abstract: A natural explanation for the carrier concentration-dependent electronic behavior in the layered cobaltates emerges within correlated-electron Hamiltonians with finite on-site and significant nearest neighbor hole-hole Coulomb repulsions. The nearest neighbor repulsion decreases hole double occupancy below hole density 1/3, but increases the same at higher hole densities. Our conclusion is valid for both single-band and three-band extended Hubbard Hamiltonians, and sheds light on concentration dependent e'(g) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 47 publications
2
13
0
Order By: Relevance
“…Layered cobaltates are unique in that ρ can be varied over a wide range by varying x . We have shown that the ρ ‐dependent electronic behavior of anhydrous Na x CoO 2 can be explained through an identical mechanism as in the CTS . In the hydrated superconducting Na‐cobaltate with x=0.35, the water enters as H 3 O + ions, and the Co valence is set by both Na doping and the amount of H 3 O + .…”
Section: The Ubiquity Of Unconventional ρ=12 Superconductorsmentioning
confidence: 90%
“…Layered cobaltates are unique in that ρ can be varied over a wide range by varying x . We have shown that the ρ ‐dependent electronic behavior of anhydrous Na x CoO 2 can be explained through an identical mechanism as in the CTS . In the hydrated superconducting Na‐cobaltate with x=0.35, the water enters as H 3 O + ions, and the Co valence is set by both Na doping and the amount of H 3 O + .…”
Section: The Ubiquity Of Unconventional ρ=12 Superconductorsmentioning
confidence: 90%
“…We have taken t > 0. Elsewhere we have argued that the U/jtj and V/jtj in the cobaltates are similar to that in the CTS [8]. With the exception of a few N e , the ground state is always in the lowest spin state (0(1/2) for N e ¼ even(odd)) for t > 0.…”
mentioning
confidence: 85%
“…Note that previous works already showed the importance of nonlocal correlations [32,33]. From a 'molecular orbitals' viewpoint, the CDW transition is driven by orbital polarization: the intersite interaction drives the symmetric orbital |u towards half-filling (hence suscep- tible to a MIT), while the two asymmetric orbitals |d 1,2 are completely filled (with in total 5 = 3(1 + y) electrons in each EKL unit cell).…”
mentioning
confidence: 90%